The Origins of Emancipation and Feminism in 19th Century India: Bengalese Experience - Tatiana G. Skorokhodova (Социологический журнал, 2021)
The development of feminism and women’s emancipation in colonial India shows various trajectories and inner sources of the process within the regions occupied by a ‘larger society’ going through modernization. The first variant appeared in colonial Bengal — a peripheral region relative to the center of Brahminical order and a place where Indian and Western culture conjoined back in the 18–19th centuries. A system of rigid constraints of women’s freedom and rights emerged within the local patriarchal society, especially in the high strata, coming from a perspective of ritual purity and men’s ‘safety’. Women themselves were bearers of traditional consciousness with stereotypes and prejudices, and they were deprived the possibility to take part in their destinies as well as social life outside of a family. Based on the works of social reformers and intellectuals, the author describes the Bengalese variant of the origins of feminism and emancipation. The primary social actor of the process was the male feminist, who publicly proclaimed ideas of women’s rights and tried to improve the lives of women through reforms. The reformatory movements led by leaders from Rammohun Roy to Keshubchandra Sen turned out to be the first wave of the emancipation process; their activity promoted the circumstances for family and social emancipatory practices. The second wave was associated with women finally becoming active and starting to speak for themselves. The main factors that stimulated their activeness were literacy and education, along with support of their aspirations of behalf of men.